FORMATION OF INFORMATION CULTURE IN STUDENTS OF ENGINEERING AND PEDAGOGICAL AREAS OF EXPERTISE DURING THEIR VOCATIONAL TRAINING - Sliusarenko Mykola; Filatov Sergiy (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The study examines the problem of the content and structure of the students’ information culture in engineering and pedagogical areas of expertise, as well as directions, methods and technologies of its formation during their professional training. The purpose of the article is to highlight the content and structure of the information culture in students of engineering and pedagogical specialities and to study the leading ways of managing its formation within the vocational training process. It has been established that information culture is complex, integrated, and value-based personal formation, a structural component of the future specialist’s professional culture. It includes a set of knowledge, skills, values and attitudes that aid in effectively perceiving, processing, understanding, evaluating, storing, producing, sharing and application of information in the modern information society, in professional activity and in teaching in educational institutions. It has been found out that information culture in its development goes through several qualitative levels, namely: cognitive (the level of awareness and functional knowledge); emotional value-based (instructions, evaluations, and attitudes); and behavioural (actual and potential cultural behaviour in working with information) ones. Following the analysis of primary sources, within the space of an individual’s information culture, the culture of educational-cognitive activity, communicative and computer cultures have been distinguished. It has been claimed that each component has independent significance and, in unity, ensures the implementation of cognitive, value-orientating, creative-developmental functions, as well as the functions of optimization, intensification, and professionalization in the students’ professional training in engineering and pedagogical area of expertise. It has been generalized that information culture assists future professionals to become active participants in the contemporary information space, effective agents of society’s digital transformation, and representatives of high professional culture and professional and pedagogical mastery. It has been emphasized that the process of shaping the information culture in students of engineering and pedagogical specialities is an integral part of their professional training, conducted based on comprehensive and interdisciplinary approaches. The main directions of such activity include: deepening the content of curriculum disciplines, expanding the content of educational and production practices, introducing special courses and electives, refining the content of students’ independent educational activities in engineering and pedagogical specialities, developing project-based and public activities of students, and in addition – networking. Practical experience in implementing programs for the formation of information culture in educational institutions of various levels has shown that such programs can be successful if they are adapted to the needs and capabilities of a specific educational organisation. Further refinement of comprehensive interdisciplinary programs for the formation of the students’ information culture is seen in its adaptation to changes in the information environment, development of interactive resources, strengthening digital security, collaboration with other organizations, and spreading awareness regarding the importance of information culture and digital literacy among all participants of the educational process. It has been concluded that managing the process of forming the information culture of students in engineering and pedagogical areas of expertise is a complex and multi-faceted task. In its implementation, it is necessary to ensure the unity, interconnection, and complementarity of all the mentioned directions, as well as to carry out direct operation (via consulting, lectures, and seminar classes) and indirect (through pedagogical conditions, established procedures, instructions, and modern SMART systems) competent pedagogical management.